PDF ANALISIS FAKTOR PRODUKSI DAN KELAYAKAN USAHATANI CABE MERAH DI KELURAHAN SEI GOHONG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA The analysis of Production Factors and feasibility of Red Chillies in in the village of Bukit Batu subdistrict Sei Gohong city of P: Rajudinnor - journal journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThis study aimed to: i) analyze the influence of factors of production to the level of farm production RedChillies, ii) determine the feasibility of farming Red Chillies during one production process, researchwas conducted in the village of Bukit Batu subdistrict Sei Gohong city of Palangkaraya. Total sample offarmers as many as 30 farmers was taken by simple random sampling (Sample Random Sampling)from the total population of Red Pepper farmers as many as 60 farmers. The analytical tool to answerthe first objective equation is used Cobb Douglas: Y = boX1b1X2b2X3b3X4b4X5b5 where Y = production(kg), X1 = land area (Ha), X2 = Seed (kg), X3 = fertilizer (kg), X4 = pesticides (liter), X5 =labor (HOK), bo= coefficient parameter. While the analytical tool used to answer the second goal used analysisRevenue Cost Ratio (RCR), which is the ratio between the total revenue with the total cost ofproduction. If RCR> 1 then farming is feasible to cultivate. The results showed that the factors ofproduction land, seed, fertilizer, pesticides and labor simultan eously affect significantly against RedChillies production in Sub Sei Gohong Bukit Batu subdistrict city of Palangka Raya. Value Fcount(97,513)> Ftable (2,409). Partially influence of each factor of production to production Red Chillies witha confidence level of 95%, the area of land with an elasticity of 0.329 (significant), seeds 0.150(significant), fertilizer 0.314 (significant), pesticides 0.140 (significant), and labor -0.020 (notsignificant). The value of Revenue Cost Ratio of Red Chili farming is 3.2. It means that everyproduction cost expense of Rp 1,000 will generate revenue of Rp 3,200, -. RCR> 1 means that RedChilli farming in Kelurahan Sei Gohong District of Bukit Batu Kota Palangka Raya is feasible orprofitable.Key word: Feasibility, Production Factor, Red Chilli Farming